2015
DOI: 10.1097/mbc.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Correcting thrombin generation ex vivo using different haemostatic agents following cardiac surgery requiring the use of cardiopulmonary bypass

Abstract: Recently, lower thrombin generation has been associated with excess bleeding post-cardiopulmonary bypass (CPB). Therefore, treatment to correct thrombin generation is a potentially important aspect of management of bleeding in this group of patients. The objective of the present study was to investigate the effects of fresh frozen plasma (FFP), recombinant factor VIIa (rFVIIa), prothrombin complex concentrate (PCC) and tissue factor pathway inhibitor (TFPI) inhibition on thrombin generation when added ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…5 In an in vitro study, PCC was found to be more potent in restoring post-CPB thrombin generation than plasma. 7 This may in part explain why the use of PCC as part of a multifaceted management of coagulopathy seems to have a greater blood-sparing effects than plasma. Supportive clinical data, however, is limited.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 In an in vitro study, PCC was found to be more potent in restoring post-CPB thrombin generation than plasma. 7 This may in part explain why the use of PCC as part of a multifaceted management of coagulopathy seems to have a greater blood-sparing effects than plasma. Supportive clinical data, however, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This conversion is consistent with in vitro observations that post-CPB impaired thrombin generation can be corrected by 15 mg kg À1 of plasma or 25 IU kg À1 of PCC. 7…”
Section: Editor's Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations